Effect of nonsolvent additive on development of polyethersulfone (PES) membrane for 02/N2 separation - Azyyati, Johari (2010)
The objectives of this study are to develop new dope formulation for producing asymmetric membrane for O2/N separation by using three different types of nonsolvent additives (NSA). Polyethersulfone (PES) asymmetric flat sheet membrane was prepared by the dry/wet phase inversion process from casting solution containing polyethersulfone (PES) as polymer, 1-methyl-2-pyrrolidone (NMP) as solvent and three different types of NSA which are water, ethanol, and methanol. The casting solutions were casted using manually casting technique. Then, the membranes were coated with silicone polymer in order to improve the membrane surface. The membranes were tested using O2 and N2 2 gases permeation test system. The morphologies of the membranes were then examined by using scanning electron microscopy (SEM). Consequently, from the pure gas permeation test results, it was found that the optimum weight percent solution containing the best nonsolvent were 27.24%wt of PES, 64.72%wt of NMP and 7.54%wt of H 0. SEM results showed the different NSA used will produce different influence on gas separation characteristics and morphologies of the produced membranes. The newly developed PES membranes with new casting solution formulation that used H22O as NSA, resulted O2/N selectivity of 3.22 and permeability of O22 gas was 11.97 GPU and permeability of N gas was 3.71 GPU. Addition of H22O as NSA resulted the lowest skin thickness compared to EtOH and MeOH which 781.5nm. Thicker of skin thickness of membranes means the chance of pinhole formation seems to be least which was contributed to high permeation of O gas and low permeation of N22 gas. Therefore, the PES membranes prepared from NMP/HO proved to provide the best separation characteristics compared to those membranes produced from NMP/EtOH solvent and NMP/MeOH solvent system. As a conclusion, it should be emphasized that the membrane of the highest flux and highest selectivity could be obtained by proper adjustment of the skin layer thickness and the sub layer morphology which was done by proper choice of nonsolvent additive. Thus, choosing the best nonsolvent additive had successfully developed asymmetric PES membranes for O2/N2 separation applications.